GOOD TOURISM GOVERNANCE DALAM PENGELOLAAN EKOWISATA MANGROVE KAMPUNG TELUK SEMANTING KABUPATEN BERAU - Wini Ananda Utamy; Elisa Susanti; Nunung Runiawati (Universitas Padjadjaran, 2023)
At present, all development in Indonesia applies the concept of sustainability, including in the tourism sector. In order to achieve this mission, the process needs to be carried out with good tourism governance. Mangrove Ecotourism itself has received various supports from three key actors, namely the government, the private sector, and the community. However, in reality the management of ecotourism has not met expectations, so it is interesting to study. The research method used is descriptive qualitative by collecting data through observation, literature study, and interviews with 9 informants involved in the management of the Teluk Semanting’s Mangrove Ecotourism. It aims to understand, analyze, and explain various aspects of existing management. The theory put forward (Sunaryo 2013) is in the form of synergistic active participation between three key actors in achieving success indicators that refer to the principles of sustainable and environmentally sound tourism development, namely active participation of related communities, involvement of all stakeholders, local ownership partnerships, sustainable use of resources. , accommodating community aspirations, environmental carrying capacity, program monitoring and evaluation, environmental accountability, training for related communities, as well as promotion and advocacy of local cultural values are used as references in this research. The results showed that the management of the Teluk Semanting’s Mangrove Ecotourism had been carried out well even though 5 out of 10 indicators were not yet optimal, in more detail in the form of a lack of human resources from the community, not yet effective communication between actors, especially the government and the private sector, some tourism resources have not been classified safe for tourists, there are no waste processing utilities and inadequate telecommunication networks, there are no records related to training, and the lack of culture and promotional information. Pada saat ini segala pembangunan yang ada di Indonesia menerapkan konsep bekerlanjutan termasuk dalam sektor pariwisata. Guna mencapai misi tersebut maka dalam prosesnya perlulah dilakukan dengan tata kelola kepariwisataan yang baik. Ekowisata Mangrove ini sendiri telah mendapat berbagai dukungan dari tiga aktor kunci yaitu pemerintah, swasta, dan masyarakat. Namun dalam kenyataannya pengelolaan ekowisata ini belum sesuai harapan sehingga menarik untuk diteliti. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan mengumpulkan data melalui observasi, studi literatur, dan wawancara dengan 9 orang informan yang terlibat dalam pengelolaan Ekowisata Mangrove Teluk Semanting. Hal ini bertujuan untuk memahami, menganalisis, dan menjelaskan berbagai aspek pengelolaan yang ada. Teori yang dikemukakan (Sunaryo 2013) berupa partisipasi aktif yang sinergis antar tiga aktor kunci dalam mencapai indikator keberhasilannya yang mengacu pada prinsip pembangunan pariwisata berkelanjutan dan berwawasan lingkungan yaitu partisipasi aktif masyarakat terkait, keterlibatan segenap pemangku kepentingan, kemitraan kepemilikal lokal, pemanfaatan sumber daya secara berlanjut, mengakomodasi aspirasi masyarakat, daya dukung lingkungan, monitoring dan evaluasi program, akuntabilitas lingkungan, pelatihan pada masyarakat terkait, serta promosi dan advokasi nilai budaya lokal dijadikan sebagai acuan dalam penelitian ini. Hasil penelitian menunjukkan pengelolaan Ekowisata Mangrove Teluk Semanting telah terlaksana dengan baik meskipun 5 dari 10 indikator yang ada belum optimal, secara lebih rincinya berupa kurangnya sumber daya manusia dari masyarakat, belum efektifnya komunikasi antar para aktor khususnya pemerintah dan swasta, beberapa sumber daya pariwisata belum tergolong aman bagi wisatawan, tidak adanya utilitas pengolahan limbah dan jaringan telekomunikasi yang belum memadai, tidak adanya pencatatan terkait pelatihan, dan minimnya budaya serta informasi promosi.